Determinant factors of the squat jump in sprinting and jumping athletes - Gonzalez-Badillo, J. J.; Jimenez-Reyes, P.; Ramirez-Lechuga, J. (Journal of Human Kinetics, 2017)
The aim of this study was to assess the relationship between strength variables and maximum velocity (Vmax) in the squat jump (SJ) in sprinting and jumping athletes. Thirty-two sprinting and jumping athletes of national level (25.4 ± 4.5 years; 79.4 ± 6.9 kg and 180.4 ± 6.0 cm) participated in the study. Vmax in the SJ showed significant relationships with peak force 1 (PF1) (r = 0.82, p = 0.001), peak force 2 (PF2) (r = 0.68, p = 0.001), PF2 by controlling for PF1 (r = 0.30, non-significant), the maximum rate of force development at peak force 1 (RFDmax1) (r = 0.62, p = 0.001), mean RFD 1 (RFDmean1) (r = 0.48, p = 0.01), mean RFD 2 (RFDmean2) (r = 0.70, p = 0.001), force at RFDmax1 (r = 0.36, p = 0.05), force at RFDmax2 (r = 0.83, p = 0.001) and force at RFDmax2 by controlling for PF1 (r = 0.40, p = 0.05). However, Vmax in the SJ was associated negatively with the ratio PF2/PF1 (r = -0.54, p = 0.01), time at peak force 2 (Tp2) (r = -0.64, p = 0.001) and maximum rate of force development at peak force 2 (RFDmax2) (r = -0.71, p = 0.001). These findings indicate that the peak force achieved at the beginning of the movement (PF1) is the main predictor of performance in jumping, although the RFDmax values and the ratio PF2/PF1 are also variables to be taken into account when analyzing the determinant factors of vertical jumping.